Forage Crops to Support Rehabilitation of Animal Husbandry in Merapi - Prawirodiputra, Bambang Risdiono (Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Merapi eruption in October 2010 caused livestock losses. To rehabilitate it, the forages demand should be fulfilled. The constraints faced in Merapi after eruption is low organic content of the soil, therefore the forages to be planted should be adapted to such condition. There are some forages recommended to be planted. For short term rehabilitation, the species recommended are those from the genus of Brachiaria, Cynodon and Pennisetum. Flemingia is also good for short term rehabilitation. For long term rehabilitation, Sesbania, Calliandra, Gliricidia and Leucaena are recommended. Key words: Land rehabilitation, grasses, legumes